Epidemiological, Therapeutic and Evolutionary Profile of the Hemorrhoidal Pathology: Experience of The Gastroenterology Department of MED VI University Hospital of Morocco - Hala, Aouroud; Hanane, El Abassi; Errami, Adil Ait; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Hemorrhoidal pathology is a benign affection occupying a special place in medical practice, posing essentially therapeutic problems. The aim of this work was to study the epidemiological, therapeutic and evolutionary characteristics of this hemorrhoidal pathology. We conducted a prospective study in the gastroenterology department of the CHU Mohamed VI of Marrakech over a period of 06 months (March 2019 - September 2019) where we collected 130 cases. The average age was 45.9 years with a clear predominance of men: sex ratio M / F = 1.95. The main reason for consultation was isolated rectal bleeding in 32% of patients. Proctologic examination revealed internal hemorrhoids, mainly stage II and stage III in 58.4% of patients, followed by external hemorrhoids in 16.9% of our patients. Paraclinically, CBC was performed in all patients with rectal bleeding and anemia was found in 17%. Thus, additional endoscopic exploration by colonoscopy was performed in 14.6% of cases returning to normal. The therapeutic management consisted primarily of hygienic and dietary measures in all our patients, 80% received drug treatment; while 25% received Instrumental rubber band ligation treatment after treatment failure, and only 16% of patients received surgical DTC. The evolution was marked by effective treatment in 78.46% of patients, while 28 patients presented minimal complications ranging from simple anal pain to a more or less extensive and serious infection. Despite the effectiveness of surgical treatment, it should be the last resort after a possible failure of medical and instrumental treatment.